Molds and Aflatoxins in Traditional Moldy Civil Cheese: Presence and Public Health Concerns - ONMAZ, NE; ÇINICIOĞLU, S; GUNGOR, C (Journal of the Hellenic Veterinary Medical Society, 2021)
The purpose of this study was to detect the mold biota, the contamination levels of total aflatoxin (AFB1, AFB2, AFG1, AFG2) and aflatoxin M1 (AFM1) in moldy civil cheese. A total of 100 moldy civil cheese were collected from randomly selected retailers. Mold biota was determined with conventional and ITS sequence analysis, and Aflatoxin (AF) analysis was performed usingEnzyme-Linled Immunosorbent Assay (ELISA). In the analyzed samples, Penicillium roqueforti (100%) was isolated as the dominant species followed by P. verrucosum (83%), Aspergillus flavus (17%). Fifteen (15 %) of moldy civil cheese samples contained AF with levels ranging from 12 to 378 ng/kg.Likewise, AFM1 was found in 25 (25 %) of samples (ranging from 5.46 to 141.56 ng/kg), among which 5 (5 %) were above the legal limits. Considering the presence of A. flavus, total AF and AFM1 contamination in the analyzed cheese samples it could be emphasized that moldy civil cheese might pose a hazard for public health.